2017
DOI: 10.3390/publications5030018
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Similarity in Academic Contexts

Abstract: Abstract:We propose some reflections, comments and suggestions about the measurement of similar and matched content in scientific papers and documents, and the need to develop appropriate tools and standards for an ethically fair and equitable treatment of authors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…Based on these reports, it was therefore reasonable to set a similarity index range of ≤10% to represent the articles with low similarity. Although many journals appear to use a similarity rate of 10% as a relevant cut‐off for any form of plagiarism, it is believed that some of them use the threshold value up to 25% or even 35%, and review articles may have higher editorial thresholds (Mahian et al, ; Meo & Talha, ). Therefore, the use of more conservative scores to classify moderate similarity and an expansive range for high similarity provides a ranking system that represents an ideal hierarchy for analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these reports, it was therefore reasonable to set a similarity index range of ≤10% to represent the articles with low similarity. Although many journals appear to use a similarity rate of 10% as a relevant cut‐off for any form of plagiarism, it is believed that some of them use the threshold value up to 25% or even 35%, and review articles may have higher editorial thresholds (Mahian et al, ; Meo & Talha, ). Therefore, the use of more conservative scores to classify moderate similarity and an expansive range for high similarity provides a ranking system that represents an ideal hierarchy for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be inferred that a threshold of similarity index ≤10% has been adopted by most of the journals included in our analysis. With 14.29% of articles recorded as moderate similarity, this may still be considered within the appropriate considerations of the journal thresholds of <25% (Mahian et al, ; Meo & Talha, ). It is safe to say that 90% of these influential articles are within the allowable plagiarism level based on this index, while 9.09% articles on average scored a high similarity (21%–50%), and none of the articles scored a very high rate (>50%) of similarity.…”
Section: Discussionmentioning
confidence: 99%
“…29 30 Another paper observed that journal editors tend to reject a manuscript if text similarity is above 10%. 31 The study on participants completing the AuthorAID MOOC on Research Writing also found that some participants reported that their institutions consider text similarity of less than 20% as acceptable. 24 As an example, the guidelines of the University Grants Commission of India allow for similarity up to 10% as acceptable or minor (Level 0), but anything above is categorized into different levels (based on the percentages), each with separate list of repercussions for students and researchers.…”
Section: Similarity Indexmentioning
confidence: 99%
“…Second, text similarity in some parts of manuscript (i.e., methods and results) should be weighed differently from other sections (i.e., introduction and discussions) and its conclusions. 31 In addition, based on the personal experience of the author of this paper, some individuals might use a sophisticated technique to avoid detection of high similarity through the use of inappropriate synonyms, jargon, and deliberate grammatical and structural errors in the text of the manuscript. Third, plagiarism of ideas may be missed by these tools as they can only detect plagiarism of words.…”
Section: Similarity Indexmentioning
confidence: 99%
See 1 more Smart Citation